Pendidikan Inklusi Dalam Pembinaan Moderasi Beragama - Deden Syarif Hidayatulloh; Fuad Hilmi (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss inclusive education in fostering religious moderation at Telkom University. This research uses descriptive qualitative method. Research subjects were selected by purposive sampling. Data collection techniques include: observation, interviews, and documentation. The research subjects were Lecturers of Religion, administrators of the University Mosque, Mentoring Tutors, Islamic student work units, and students. Data analysis techniques using data collection, data reduction, data display, and verifying. The results and discussion of this study indicate that inclusive education implemented at Telkom University creates religious moderation within Telkom University. This is evidenced by the verification of the data with the data assessment rubric, that the results of observations, interviews, and documentation show that the development of religious moderation at Telkom University is through inclusive education. This study concludes that inclusive education is very appropriate in fostering religious moderation.